The effect of desiccation cracks on water infiltration in landfill cover under extreme climate scenarios - Apriyono, Arwan; Yuliana, Yuliana; Kamchoom, Viroon; Leung, Anthony Kwan; Jotisankasa, Apiniti; Liangtong, Zhan (My University, 2025)
Predicting water infiltration in clay poses a significant challenge, primarily due to the presence of desiccation cracks, which are amplified by extreme climate. Accurate methods for calculating water infiltration, considering crack variations under extreme climates are essential especially for landfill covers. The objective of this study is to explore the relationship between crack intensity factor (CIF) and water infiltration in high-plasticity clay, focusing on seasonal changes and extreme climate conditions. A series of double-ring infiltration tests was conducted in the field to observe the impact of desiccation cracks on water infiltration. Subsequently, a modified Green–Ampt method incorporating CIF was developed and validated against these field test results to improve water infiltration predictions. This study revealed that the maximum CIF was notably higher in the second dry season (11.4 %) than that in the first one (8.1 %), indicating soil structural degradation. An exponential correlation was observed between increased CIF and infiltration rates, attributed to cracks creating preferential pathways. In extreme climate scenarios, CIF increases could surpass 15 %, potentially elevating soil's saturated hydraulic conductivity (Ks) by over 85 % relative to current climate conditions.
Keywords: Bangkok clay; Crack propagation; Double-ring infiltration test; Future climate; Infiltration rate